Effect of Shielding Gas on the Microstructure and Properties of Laser-MAG Hybrid Welded Joint for Nickel-Saving Stainless Steel. (25th March 2022) - Fang, Naiwen; Huang, Ruisheng; Wang, Xingxing; Tian, Jiahao; Li, Shuai; Wu, Pengbo; Xu, Kai; He, Peng; Wen, GuoDong; Jiang, Laizhu
Abstract : Laser-MAG (metal active gas) hybrid welding of nickel-saving 08Cr19Mn6Ni3Cu2N stainless steel was carried out by using 98%Ar + 2%N2 and 95%Ar + 5%CO2 as shielding gases. The effect of different shielding gases on the microstructure and properties of the welded joints was investigated. The results showed that arc shrinkage was significant with the addition of nitrogen, weld spatter increased with the expansion of arc volume, and arc stability deteriorated. The ferrite content in the weld decreased by about 60%, the ferrite dendrite also gradually became finer, and the secondary dendrite arm was shorter. Only a small amount of δ and γ phases existed in the weld, and no precipitation of the σ phase and nitride was found. Observing four crystal planes, we found that size of the austenite grains decreased with the addition of nitrogen. The average tensile strength of the welded joints decreased from 712 MPa to 704 MPa, but with improved corrosion resistance, the pitting corrosion rate increased from 19.45 g·m 2 /h to 18.72 g·m 2 /h, and the hardness of weld was slightly reduced.